The Effects of Combined Exercise on Health-Related Fitness, Endotoxin, and Immune Function of Postmenopausal Women with Abdominal Obesity - Sung-Mo Park; Yi-Sub Kwak; Jin-Goo Ji (Journal of Immunology Research)
This study was conducted to examine the effects of combined exercise on health-related fitness, endotoxin concentrations, and immune functions of postmenopausal women with abdominal obesity. 20 voluntary participants were recruited and they were randomly allocated to the combined exercise group (n=10) or the control group (n=10). Visceral obesity was defined as a visceral-to-subcutaneous fat ratio ≥0.4 based on computed tomography (CT) results. Body composition, exercise stress testing, fitness measurement, CT scan, and blood variables were analyzed to elucidate the effects of combined exercise. The SPSS Statistics 18.0 program was used to calculate means and standard deviations for all variables. Significant differences between the exercise group and control group were determined with 2-way ANOVA and paired t-tests. The exercise group’s abdominal obesity was mitigated due to visceral fat reduction; grip strength, push-ups, and oxygen uptake per weight improved; and HDL-C and IgA level also increased, while TNF-α, CD14, and endotoxin levels decreased. Lowered TNF-α after exercise might have an important role in the obesity reduction. Therefore, we can conclude that combined exercise is effective in mitigating abdominal obesity, preventing metabolic diseases, and enhancing immune function.